The Physical Education Learning in Municipal Yongkang Junior High School Taiwan - Febriyani, Sri; Wen, Cheng Yun (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2018)
The objective of this research is to know the descriptive result of curriculum, process learning, infrastructure and facilities, educators, and learners in Tainan Municipal Yongkang Junior High School Taiwan. The method research is used descriptive qualitative. The data collection techniques were observation, interview, data searches and documentation. The data analysis used data reduction, data serve, and result conclusion. The results showed the used curriculum is the curriculum-based school. The learning process is carried out with the stage of planning and execution. The availability of sufficient infrastructure and facilities both in quantity as well as quality. Educators have met the qualification standards, competency standards, and test the feasibility of a teacher. Learners are required to pay for the operational cost and other unit adapted to the economic level of the family